The Role of Islamic Organizations 'Muhammadiyah and Nahdlatul Ulama' in Forming National Politics in Indonesia - Abdullah M. Al-Ansi; Rinikso Kartono (Britain International for Academic Research (BIAR-Publisher), 2023)
Unlike many of Islamic organizations, where they have some international agenda, Islamic social organizations in Indonesia have unique characteristics allowed them to play an important role in Indonesian society. Although, Muhammadiyah and Nahdlatul Ulama have some differences in basic thoughts and mechanism of actions but they are in the same competition to serve the society. This specific case made these two organizations more long lasting and trustworthy. This study included explanation of values, political characteristics and feature of these two Islamic organizations in addition to the role of both of them in shaping political aspects in Indonesia. This study was conducted by adopting qualitative approach through interviews with regional leaders and scholars in East Java Province. Narrative approach was used to finalize the results and writing report. This study reveals the political role of Muhammadiyah and Nahdlatul Ulama through forming political parties, participation in election, adopting Pancasila, education, economic activities, and religious occasions in shaping the political identity in the country. The formers, scholars, regional leaders of both organizations have an effect on followers and society to choose representatives in DPR (People’s representative council), MPR (People’s consultative assembly) and DPD (Regional representative council).